The effects of Nordic walking on cognitive function in older adults: a systematic review and meta-analysis - Li, Haobai; Zhu, Ke; Gan, Jianyu; Wang, Ziyi; Gao, Zhikun; Liu, Liangru; Guo, Xiaojie; Niu, Jianfeng (Frontiers in Aging Neuroscience, 2025)
ObjectivesNordic walking (NW), as a specialized form of aerobic exercise, emerges as a promising strategy to improve the cognitive function in older population. However, the effectiveness of NW has yet to be definitively confirmed due to the variances in the study designs and observations. This systematic review and meta-analysis was thus conducted to examine the effect of NW interventions on cognitive function of older adults.MethodsThe search was conducted in August 2025 on Web of Science, PubMed, SPORT-Discus, Medline, the Cochrane Library, Scopus, and PsycINFO databases. Two reviewers independently reviewed the search results, extracted the data, and assessed the risk of bias and certainty of evidence. Meta-analyses and meta-regressions were performed to determine the overall effect size and the impact of potential moderators.ResultsInitial screening identified 336 records, and after full-text assessment, eight studies (from 2014 to 2024) comprising 327 participants (71.19 ± 5.44 yrs) were included. The effect size of NW on executive function was significant [Hedges’ g = 0.89, 95% CI (0.27, 1.50), p = 0.01], while the effects were non-significant for global function, memory function, attention, information processing, and perceptual ability (p > 0.05). Subgroup analysis indicated that the health conditions of participants and the types of control groups significantly moderated executive function. Specifically, NW showed significant improvements (i) in older adults with health conditions and (ii) compared with inactive control groups (p = 0.04). Meta-regression revealed a significant positive correlation between the total intervention time of NW and its effect size (p < 0.01).ConclusionThis systematic review and meta-analysis demonstrates that NW interventions could improve executive function in older adults, especially those with health conditions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42025638467.